2011
DOI: 10.1089/brain.2010.0001
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Functional Connectivity in Young Women with Borderline Personality Disorder

Abstract: Borderline personality disorder (BPD) is a complex psychiatric disorder that involves the core feature of affect dysregulation. Prior neuroimaging studies have indicated that BPD patients have (1) excessive amygdala activation to negative emotion and (2) diminished frontal regulation. This study examined amygdala functional connectivity in 12 women with BPD and 12 matched healthy comparison volunteers. We explored how connectivity patterns would change in the context of processing neutral, overt fear, or maske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 50 publications
5
54
0
2
Order By: Relevance
“…It also agrees with the ancillary analysis showing increased connectivity between the left hippocampus and amygdala cluster (derived by ALFF) and a single small frontomedial cluster. All of these findings agree with the study by Cullen et al (15), which observed increased connectivity between a priori selected amygdala regions of interest and perigenual cortex under overt fear stimuli. Increase in GBC in the anterior cingulate is also relevant because this area is a core node of the default mode network (63).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It also agrees with the ancillary analysis showing increased connectivity between the left hippocampus and amygdala cluster (derived by ALFF) and a single small frontomedial cluster. All of these findings agree with the study by Cullen et al (15), which observed increased connectivity between a priori selected amygdala regions of interest and perigenual cortex under overt fear stimuli. Increase in GBC in the anterior cingulate is also relevant because this area is a core node of the default mode network (63).…”
Section: Discussionsupporting
confidence: 92%
“…It has also been shown that the experimental disruption of these connections leads to behavioral patterns similar to those observed in individuals with BPD (14). This evidence has led to the performance of functional magnetic resonance imaging (MRI) studies of connectivity in BPD, which also have reported significant alterations (15,16). However, similar to volumetric studies, the scope of such connectivity results is restricted by the prior selection of brain areas of interest.…”
mentioning
confidence: 99%
“…In a similar set of studies, Cullen and colleagues [107,108] used a task in which participants saw emotional faces masked (that is, the emotion was displayed so quickly as to be imperceptible) and overt (where the participants could consciously perceive the emotional stimuli). They found increased amygdala activation during passive, overt emotional face viewing, but not when the faces were masked.…”
Section: Neural Network Emotion Recognition and Sensitivity And Bpdmentioning
confidence: 99%
“…They found increased amygdala activation during passive, overt emotional face viewing, but not when the faces were masked. Cullen et al [108] used a method for assessing task-based functional connectivity called psychophysiological interactions (PPI), in order to determine whether there were group differences in amygdala patterns of co-activation with other brain regions over the course of the task. They found increased functional connectivity between the amygdala and the rostral ACC during overt fear processing and increased amygdalasubcortical connectivity during masked fear processing.…”
Section: Neural Network Emotion Recognition and Sensitivity And Bpdmentioning
confidence: 99%
“…During processing of emotional stimuli, Dudas et al (9) reported greater functional connectivity when viewing emotion-inducing images depicting disgust in adults with BPD between the left amygdala and left dorsolateral PFC, and left amygdala and ventral striatum. Cullen et al (10) examined functional connectivity of the amygdala to neutral, overt fearful, and masked fearful facial expressions, finding lower connectivity between bilateral amygdalae and midcingulate cortex to neutral faces in BPD. In contrast, BPD showed higher bilateral amygdalae and ACC coupling to overt fearful faces, and higher right amygdala and bilateral thalamus and caudate coupling to masked fear faces.…”
Section: Introductionmentioning
confidence: 99%